Loop Diuretics and Sarcopenia: A Potential Association - Karakousis, Nikolaos D.; Georgakopoulos, Petros N. (Muscles, 2023)
Background: Loop diuretics (LDs) are used to treat various health conditions including heart failure (HF), liver cirrhosis, and chronic kidney disease (CKD). Sarcopenia is a skeletal muscle health issue related to the depletion and decrease of muscle mass and strength, leading to adverse outcomes including frailty syndrome, functional decline, falls, hospitalizations, augmented length of hospital stay, and increased morbidity and mortality. Methods: This study investigated the probable association between LD use and sarcopenia via conducting a non-systematic review of the existing literature. Results: In subjects with non-dialysis-dependent chronic kidney disease (NDD-CKD), an augmented risk of sarcopenia is significantly associated with LD use. Interestingly, in patients with HF treated with LDs, thigh and arm circumferences were significantly small, which is indicative of skeletal muscle wasting. Additionally, in anorexic subjects who are more likely to be on diuretic medication, suffering also from cachexia, a higher prevalence of sarcopenia was demonstrated. In cirrhotic subjects, the treatment dosage of LDs was inversely correlated with the skeletal muscle area per year (ΔSMA). Nevertheless, in subjects with liver cirrhosis treated with LDs, who were divided into those with and those without muscle cramps, the presence of sarcopenia was similar. Conclusions: Further investigation is imperative to validate potential interplay between LDs and sarcopenia.